Egypt, Islam, and the Arabs : the Search for Egyptian Nationhood, 1900-1930. - Gershoni, Israel (Studies in Middle Eastern history., 1986)
Throughout the 20th century, Egyptian nationalism has alternately revolved around three primary axes: a local Egyptian territorial nationalism, a sense of Arab ethnic-linguistic nationalism, and an identification with the wider Muslim community. This detailed study is the first to systematically examine Egyptian territorial nationalism as both ideology and praxis--from the ascendancy of an exclusively Egyptianist national orientation during World War I to the intellectual and political dimensions of the phenomenon as it flourished in the interwar years.